Jenis Kesulitan Menulis Puisi bagi Peserta Didik di Sekolah Dasar - Rahmawati, Debby; Citrawati, Tyasmiarni (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
This study aims to determine the types of difficulties students in class IV of elementary school in writing poetry texts. This research uses a qualitative approach with descriptive methods. The subjects of this study were teachers and fourth grade students at Muhammadiyah 2 Socah Bangkalan Elementary School. The process of collecting data carried out by the method of tests and interviews. The results of this study are that students encountered some difficulties in writing poetry texts. Difficulties that often occur in writing poetry include difficulty in determining diction such as word management that is not appropriate, typographical difficulties in spelling regularity or letters that are difficult to read so that they are less attractive, difficulty in determining figurative language in the power of expression, difficulty in determining rhyme in determining sound placement and repetition, and difficulty determining the tone in the atmosphere of the poem you want to convey. The difficulties that are classified as the most difficult for students are in the elements of diction and rhyme, and the lightest difficulty is in determining the mandate.